The effect of passive music intervention on health-related quality of life after tonsillectomy - Zaubitzer, Lena; Waßmer, Felix; Kramer, Benedikt; Lammert, Anne; Sadick, Haneen; Schell, Angela; Scherl, Claudia; Rotter, Nicole; Häussler, Daniel (Annals of otology, rhinology & laryngology, 2025)
Introduction: Measurement of health-related quality of life (QoL) is a firmly established method for evaluating therapeutic procedures. Studies have demonstrated positive effects of passive music interventions. To date, however, no standardized approach to music therapy interventions after head and neck surgery has been developed. Furthermore, the effects of such interventions in the immediate postoperative phase following surgery in head and neck region have yet to be adequately investigated. - Methods: Patients undergoing tonsillectomy were consecutively included in a prospective randomized study. The intervention group received passive music therapy (60 minutes/day). QoL was recorded using the Glasgow Benefit Inventory (GBI) and Brief Pain Inventory (BPI) at 3 fixed time points after operation. In addition, the participants filled out a pain diary throughout the observation period using a Visual Analog Scale. - Results: Study sample comprised 31 patients. Fifteen patients (6 women and 9 men) were included in the intervention group and 16 (6 women and 10 men) in the control group. Participants’ average ages were 28 years (intervention group) and 39 years (control group). Significant differences in QoL emerged 5 and 14 days after surgery (P = .049 and <.01). In addition, the BPI results differed significantly at time point 3 (P < .01). Significant differences were observed in the pain diary from day 8 after surgery. - Discussion/Conclusion: Complementary music interventions may improve QoL as well as patients’ pain perception. Owing to its ubiquitous availability and cost-effectiveness, passive music interventions with their measurable positive benefits may be easily implemented into clinical routine.
Gesehen am 04.09.2025